Indikator Sosial Ekonomi Wilayah Dan Ketahanan Pangan Rumah Tangga Perempuan Miskin Di Aceh - Suyanti Kasimin (Program Studi Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala, 2015)
ABSTRACT. This study aimed to analyze the socio-economic indicators of the domicile of poor women and their relationship to the level of income, level of welfare and the level of household food security of poor women. The analytical method used, descriptive analysis of the socio-economic region characteristics for poor women, multiple regression analysis and correlation to analyze the factors that affect the level of income, level of welfare and the level of household food security of poor women. The analysis showed that 69,3 percent of poor women of childbearing age, with 89 percent and 59,8 percent less educated work as laborers and selling snacks. Factors influencing the level of income is age, education level and occupation, while the factors that affect the well-being is the condition of the house, the problems they face, as well as the income that they have. Furthermore, the level of household food security of poor women affected by family size, income level and the level of welfare that they have.